Effect of hygrothermal environment on tensile properties of carbon fiber epoxy resin composites - DU Yong; MA Yu′e (Xibei Gongye Daxue Xuebao, 2022)
[0]16, [90]16, [±45]4s and [+45/0/0/-45/-45/0/0/+45]s were fabricated to study the influence of the different ply lay-up on the moisture absorption and tensile properties of TG800/E207 carbon fiber epoxy resin composite laminates at a hygrothermal environment of 80℃ and 90%RH. Moisture absorption curves, damage morphology after moisture absorption, fracture morphology, load-displacement curves and strength degradation were analyzed. The results show that the moisture absorption curves of TG800/E207 composite laminates present multi-stage phenomenon. The moisture adsorption reached equilibrium at a moisture absorption time of 1 608 hours. The equilibrium moisture content of [90]16 is the lowest and its saturated moisture content is only 0.806%; the equilibrium moisture content of [+45/0/0/-45/-45/0/0/+45]s is the highest and its saturated moisture absorption rate is 0.876%. The failure load of [0]16, [90]16, [±45]4s and [+45/0/0/-45/-45/0/0/+45]s samples decreased by 13.8%, 27.36%, 10.7% and 25.6%, respectively. The saturated moisture absorption of [90]16 is the lowest, but its tensile strength degradation is the most serious.